Investigation of a Bragg grating-based Fabry-Perot structure inscribed using femtosecond laser micromachining in an adiabatic fiber taper - Madan, Aayush (2021)
This paper presents the fabrication of a fiber Bragg grating (FBG)-based Fabry-Perot (FP) structure (7 mm total length) in an adiabatic fiber taper, investigates its strain and temperature characteristics, and compares the sensing characteristics with a standard polyimide coated FBG sensor. Firstly, a simulation of the said structure is presented, followed by the fabrication of an adiabatic fiber taper having the outer diameter reduced to 70 μm (core diameter to 4.7 μm). Next, the sensing structure, composed of two identical uniform FBG spaced apart by a small gap, is directly inscribed point-by-point using infrared femtosecond laser (fs-laser) micromachining. Lastly, the strain and temperature behavior for a range up to 3400 με and 225 °C, respectively, are investigated for the fabricated sensor and the FBG, and compared. The fabricated sensor attains a higher strain sensitivity (2.32 pm/με) than the FBG (0.73 pm/με), while both the sensors experience similar sensitivity to temperature (8.85 pm/°C). The potential applications of such sensors include continuous health monitoring where precise strain detection is required.